Rancang Bangun Sistem Informasi Pengelolaan Aset Elektronik Kantor Berbasis Website Pada PT Maju Aman Sejahtera - Muhammad Hisyam (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Electronic asset management across 144 outlets of PT Maju Aman Sejahtera still faces problems because asset condition recording relies on paper forms, photographs, Gmail, and Microsoft Excel. This process creates repetitive work, increases the potential for human error, and makes it difficult for the General Affairs Division to obtain up-to-date asset condition information. This study aims to design and develop a website-based electronic asset management information system that centralizes asset data, digitizes asset requests, supports stock taking, and improves reporting accuracy. The system was developed using the Rapid Application Development (RAD) method with CodeIgniter 3, PHP, and MySQL. Data were collected through observation, interviews, and literature study. The resulting system provides login, user management, outlet management, asset type management, asset data management, asset requests, stock taking, asset condition monitoring, reporting, notifications, and logout functions. QR Code technology is used as a unique asset identity to support physical verification and stock-taking activities. Alpha testing showed that the system functions operated according to the test scenarios, while beta testing produced an overall feasibility score of 84.18%, categorized as highly feasible. The results indicate that the developed system can support the digitalization of electronic asset management and reduce dependence on manual processes